Persistent Pulse Generator - Johar, Muhammad Ameerul Haeqal; Khamal, Muhammad Kamarul Adam; Haslinizam, Haikal Ammar; Othman, Khairulnizam (Multidisciplinary Applied Research and Innovation, 2025)
The need for reliable and portable power sources is paramount in today's dynamic and mobile society, particularly in agricultural settings. This research addresses the challenge faced by sugarcane farmers in Ayer Hitam, Johor, who struggle with "Top Borrer" insect attacks on sugarcane stalks. Traditional methods using Haloline Eco Double-ended halogen lamps powered by fuel generators are inefficient due to noise and smoke emissions. This study explores the development of a more sustainable and effective power solution utilizing the principles of magnet and solenoid coil interaction to generate electricity. Through the design and implementation of the Persistent Pulse Generator, which operates without continuous external power sources, we aim to provide a reliable and eco-friendly power alternative. The research employs a comprehensive design methodology, material selection, and engineering analysis to develop the generator. The main findings show that the Persistent Pulse Generator significantly reduces operating costs and enhances the effectiveness of pest control measures. This project concludes that this innovative approach can greatly improve agricultural productivity and sustainability by offering a cleaner and more efficient power source for pest management.